2018
DOI: 10.1002/ana.25156
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal deep brain stimulation modulates cortical excitability and plasticity

Abstract: Single-pulse DBS modulates cortical excitability and plasticity at specific time intervals. These effects may be related to the mechanism of action of DBS. Combination of DBS with cortical stimulation with appropriate timing has therapeutic potential and could be explored in the future as a method to enhance the effects of neuromodulation for neurological and psychiatric diseases. Ann Neurol 2018;83:352-362.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 50 publications
(233 reference statements)
1
56
0
Order By: Relevance
“…Although these newly proposed connections still need further confirmation, the evidence is getting stronger. In addition to our study, which used cortical evoked potentials and transcranial magnetic stimulation, tractography with diffusion magnetic resonance imaging and coherence between local field potential from the GPi and electroencephalography/magnetoencephalography are consistent with a direct connection between the GPi and cortical areas. Given that GPi is the major output nucleus of basal ganglia and is a common target for deep brain stimulation, the scientific and clinical importance of the potential existence of a pallidocortical pathway is clear.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Although these newly proposed connections still need further confirmation, the evidence is getting stronger. In addition to our study, which used cortical evoked potentials and transcranial magnetic stimulation, tractography with diffusion magnetic resonance imaging and coherence between local field potential from the GPi and electroencephalography/magnetoencephalography are consistent with a direct connection between the GPi and cortical areas. Given that GPi is the major output nucleus of basal ganglia and is a common target for deep brain stimulation, the scientific and clinical importance of the potential existence of a pallidocortical pathway is clear.…”
supporting
confidence: 82%
“…Given that GPi is the major output nucleus of basal ganglia and is a common target for deep brain stimulation, the scientific and clinical importance of the potential existence of a pallidocortical pathway is clear. However, projections in both directions (GPi→cortex and cortex→GPi) have been reported in animal studies, and the technique used in recent human studies could not determine the direction of projections . Moreover, the neural transmitters involved in the pallidocortical pathway are not known.…”
mentioning
confidence: 99%
“…The existence of a direct cortico‐pallidal connection is also corroborated by the presence of a robust band of beta coherence between the sensorimotor areas and GPi in dystonic patients with GPi‐DBS . On the other hand, we cannot exclude the possible involvement of cholinergic facilitatory neurons, which are dispersed around the GPi …”
mentioning
confidence: 79%
“…We read with great interest the article published by Ni et al reporting the effect of pallidal deep brain stimulation (DBS) on cortical excitability and plasticity in patients with primary cervical dystonia . Interestingly, the authors found two peaks (the first with a latency of ∼10ms and the second of ∼25ms) of cortical evoked potentials in the ipsilateral motor cortical areas in response to internal globus pallidus (GPi)‐DBS.…”
mentioning
confidence: 99%
“…The intended therapeutic and unintended side effects of DBS are likely mediated through multiple mechanisms, potentially driven by multiple cell-types, that alter the function of a neural circuit. The relative contribution of each mechanism may evolve over the course of stimulation due to changes in the electrode/tissue interface 28,29 , stimulation induced plasticity in neuronal and non-neuronal cells near the electrode 30 , stimulation induced post-synaptic plasticity 31 , changes in behavior state 32 , and adjunct drug status 33 . Clinical use of neuromodulation therapies in diverse conditions such as epilepsy, depression and Tourette's syndrome consistently demonstrate significant improvement in patient outcomes with slow onsets over periods of several weeks to several months 11,[34][35][36][37][38][39][40][41][42] .…”
Section: Introductionmentioning
confidence: 99%